2023
DOI: 10.3389/fgene.2022.1077615
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and pan-cancer system analysis identify PM2.5-induced stanniocalcin 2 as a potential prognostic and immunological biomarker for cancers

Abstract: Epidemiological studies have shown that air pollution and particulate matter (PM) are closely related to the occurrence of cancer. However, the potential prognostic and immunological biomarkers for air pollution related cancers are lacking. In this study, we proved PM2.5 exposure was correlated with lung cancer through transcriptome analysis. Importantly, we identified STC2 as a key gene regulated by PM2.5, whose expression in epithelial cells was significantly increased after PM2.5 treatment and validated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Mechanistically, long-term exposure of lung cancer cells to PM 2.5 may promote lung cancer progression through activation of the Aryl hydrocarbon receptor (AhR) and epidermal growth factor receptor (EGFR), which boosts the Serine protease pathway transmembrane 2 (TMPRSS2)-IL8 pathway. STC2 induced by PM 2.5 could be a potential immunological biomarker not only for the prognosis of lung cancer but also additional cancers related to air pollution ( Zhu et al, 2023 ). It has also been shown that human epithelial cells exposed to PM 2.5 are more susceptible to hypomethylation and transcriptional activation of several coding genes as well as microRNA, which induces modified signaling pathways related to cancer ( Heßelbach et al, 2017 ).…”
Section: Pm-induced Dna and Histone Modifications Within The Context ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanistically, long-term exposure of lung cancer cells to PM 2.5 may promote lung cancer progression through activation of the Aryl hydrocarbon receptor (AhR) and epidermal growth factor receptor (EGFR), which boosts the Serine protease pathway transmembrane 2 (TMPRSS2)-IL8 pathway. STC2 induced by PM 2.5 could be a potential immunological biomarker not only for the prognosis of lung cancer but also additional cancers related to air pollution ( Zhu et al, 2023 ). It has also been shown that human epithelial cells exposed to PM 2.5 are more susceptible to hypomethylation and transcriptional activation of several coding genes as well as microRNA, which induces modified signaling pathways related to cancer ( Heßelbach et al, 2017 ).…”
Section: Pm-induced Dna and Histone Modifications Within The Context ...mentioning
confidence: 99%
“…Renal, cardiac, liver and pulmonary fibrosis are the major causes of death, but several studies have identified common altered epigenetic regulation that could be a potential approach to target multi-organ fibrosis ( Rubio et al, 2023b ). Particularly, pulmonary fibrosis (PF) is the irreversible phenotype of all interstitial lung diseases (ILDs), characterized by progressive thickening of lung tissue that reduces gas exchange and ultimately leads to progressive hypoxemia, respiratory failure, and mortality ( Zhu et al, 2023 ). PF is an age-related ILD characterized by a failure in lung alveolar epithelial regeneration and an abnormal wound-healing response ( Chanda et al, 2019 ).…”
Section: Pm-induced Dna and Histone Modifications Within The Context ...mentioning
confidence: 99%
“…The liver can metabolize and decompose endogenous and exogenous substances, and lipid metabolism disorders can cause fatty liver, hepatitis and other liver diseases. Epidemiological studies have shown that PM 2.5 is not only closely related to cardiopulmonary diseases, the immune system and the nervous system [14][15][16], but also related to the incidence of liver cancer. Studies have shown that PM 2.5 and its binding compounds are deposited and metabolized in the liver, which may eventually cause liver damage [17].…”
Section: Introductionmentioning
confidence: 99%